1972
DOI: 10.2113/gsecongeo.67.8.1128
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Account of Chemical Relationships Between Sulfide Lode and "Banded Iron Formation" At Broken Hill, New South Wales

Abstract: As in many other districts of similar mineralization, the apparently stratiform sulfide orebodies of "Broken Hill type" at and around Broken Hill are almost invariably accompanied by thin beds of iron-rich sedimentary rock, loosely designated "banded iron formation." Representative occurrences of Broken Hill sulfide ore and iron formation have been systematically analyzed as whole rocks, and a preliminary account and comparison of their chemical constitutions is now given. The constitutional evidence supports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

1975
1975
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 0 publications
3
18
0
Order By: Relevance
“…Measurements on Pb isotopes in samples of galena from Huaripampa and Carahuacra show Ph-isotopic ratios which are close to those of the orogenic growth curve (Gunnesch and Baumann 1986;Fontbote et al, this Vol.). Similar observations were also made on Ph-isotopic measurements on other stratiform Pb-Zn deposits (Stanton 1972a;Large 1980;Gustafson and Williams 1981). 7.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Measurements on Pb isotopes in samples of galena from Huaripampa and Carahuacra show Ph-isotopic ratios which are close to those of the orogenic growth curve (Gunnesch and Baumann 1986;Fontbote et al, this Vol.). Similar observations were also made on Ph-isotopic measurements on other stratiform Pb-Zn deposits (Stanton 1972a;Large 1980;Gustafson and Williams 1981). 7.…”
Section: Discussionsupporting
confidence: 76%
“…5. The presence of banded ironstones as they also occur in other stratiform Pb-Zn deposits (Anhaeuser and Button 1976;Stanton 1972b;Stanton and Vaughan 1979;Derry et al 1965;Saif 1980). 6.…”
Section: Discussionmentioning
confidence: 97%
“…Many workers (inter alia RAMDOHR, 1950;KING, 1958;SEGNIT, 1961;CARRUTHERS, 1965;LAWRENCE, 1967;STANTON, 1972;BOTH, 1973;HODGSON, 1974) have suggested that the orebodies have been metamorphosed to a high grade with the enclosing host rocks and were probably originally stratiform.…”
Section: Introductionmentioning
confidence: 99%
“…The source of the ore-forming fluids is a point of current debate: many workers support a volcanic-exhalative model for the formation of the ores (e.g. Stanton 1972;Plimer 1979;Willis et al 1983) in which hydrothermal ore fluids are derived from magmatic and meteoric sources. Other models favour a sedimentary-exhalative origin for the ores because of the lack of any recognisable footwall stockwork zone and the predominance of metasedimentary over metavolcanic rocks in the orebearing sequence and in the overlying rocks (e.g.…”
mentioning
confidence: 99%
“…The succession include several hundred small base metal sulphide deposits, as well as the giant Willis et al 1983). Several sulphur isotope studies have been undertaken for the Broken Hill ores (Stanton andRafter 1966, 1967;Both and Smith 1975;Spry 1987), Broken Hill-type mineralisation (Both and Smith 1975) and vein-type mineralisation elsewhere in the Willyama Supergroup (Dong et al 1987). 634S values for the Broken Hill ores and for Broken Hill-type mineralisation show a fair degree of consistency and cluster around, or are slightly greater than 0%oo.…”
mentioning
confidence: 99%